Visual Language and Identity in Digital Youth Culture: A Socio-Semiotic Study of Memes among Indonesian Gen Z - Halim, Syaiful; Sari, Mita (Communica : Journal of Communication, 2024)
Memes have emerged as a powerful communicative tool among Generation Z, particularly in Indonesia where digital media usage is high. This study investigates how Indonesian Gen Z utilizes memes as socio-semiotic devices for identity construction, social critique, and cultural expression. Employing a mixed-methods approach, the research combines a quantitative survey of 72 respondents with qualitative interviews to uncover the communicative functions, rhetorical strategies, and cultural dynamics involved in meme usage. The methodology involved structured questionnaires to assess platform use, meme frequency, and perceived communicative intent, alongside thematic analysis of interview data to identify semiotic devices such as juxtaposition, parody, and visual enthymeme. Findings indicate that memes are widely used for humor, information, critique, and emotional connection, with platform features significantly shaping usage patterns. Results show that Indonesian Gen Z uses memes not only to entertain but to articulate collective identity, challenge authority, and respond to current events. These expressions are shaped by cultural codes, generational values, and visual literacy, making memes a vital mode of informal public discourse. The discussion highlights the importance of localized meme analysis and suggests integrating meme literacy into digital education to foster critical engagement with media. This research contributes to digital communication and semiotics by demonstrating that memes serve as dynamic platforms for multimodal expression, public commentary, and identity negotiation. As digital artifacts, memes are central to understanding contemporary youth discourse and the sociocultural landscapes they inhabit.